A tree is nice - Udry, Janice May (HarperCollins Publishers, 1984)
"Trees are very nice," says Janice May Udry in her first book for children. She goes on to explain that even one tree is nice, if it is the only one you happen to have. Some of the reasons why trees are good to have around are funny. Some are indisputable facts. But in all of them there is a sense of poetic simplicity and beauty which will be sure to entrance any young child. Whether he knows one tree or many, he will relish the descriptions of the delights to be had in, with, or under a tree. Marc Simont's joyous pictures, half of them in full color, accentuate the child-like charm of the words. And each painting of a tree or trees shows just how very nice they can be." --